Associations between Concurrent Substance Use and Anabolic-Androgenic Steroid Use among Adolescents. (7th June 2022) - Ganson, Kyle T.; Testa, Alexander; Jackson, Dylan B.; Nagata, Jason M.
Abstract: Background: Concurrent use of e-cigarettes, cigarettes, and cannabis is common among adolescents, while illicit anabolic-androgenic steroid (AAS) use has recently been on the rise. Today, no known research has investigated the patterns of concurrent substance use and AAS use among adolescents in the United States. Objective: To determine the association between concurrent lifetime use of e-cigarettes, cigarettes, and cannabis and illicit AAS use among adolescents. Methods: Cross-sectional data from the 2019 Youth Risk Behavior Survey ( N = 13, 677) were analyzed in 2021. Four mutually exclusive categories of concurrent substance use (no use, any single use, any dual use, and triple use) were constructed, along with any lifetime AAS use. One logistic regression model was estimated to determine the association between concurrent substance use and lifetime AAS use. Results: Compared to no use, lifetime triple use (adjusted odds ratio 3.95, 95% confidence interval 1.73–8.95) was associated with lifetime AAS use while adjusting for potential confounders. Conclusions: Findings underscore an overlapping pattern of problematic substance use that may be harmful for adolescents. Health care professionals should be aware of these patterns to improve substance use assessment protocols.